2018
DOI: 10.1002/app.47387
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic degradation, electronic, and thermal properties of graphite‐ and graphene oxide‐filled biodegradable polylactide/poly(ε‐caprolactone) blend composites

Abstract: Commodity polymers are the most widely used materials for electronic packaging applications. However, they are nondegradable and causing serious environmental damage. Addressing this challenge, the relative effects of graphite (G) and graphene oxide (GO) dispersion on the enzymatic degradation, electronic properties, thermal degradation, and crystallization behavior of enzyme degradable polylactide/poly(ε-caprolactone) blend composites is investigated. Owing to the oxygenated surface functionalities and excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Similar trends were seen in other works, though the brittle-ductile transition happens at higher PCL contents. [15,16,37] Regarding the impact strength, PLA displays a value of 22 J m −1 , another demonstration of its inherent fragility, whereas PCL does not break under the testing conditions employed in this work. The impact strength of the noncompatibilized PLA/PCL blends does not significantly change until 30 wt.% of PCL is added to PLA, a composition that shows a value almost double to that of neat PLA.…”
Section: Reference Noncompatibilized Pla/pcl Blends: Influence Of Pcl...mentioning
confidence: 79%
See 2 more Smart Citations
“…Similar trends were seen in other works, though the brittle-ductile transition happens at higher PCL contents. [15,16,37] Regarding the impact strength, PLA displays a value of 22 J m −1 , another demonstration of its inherent fragility, whereas PCL does not break under the testing conditions employed in this work. The impact strength of the noncompatibilized PLA/PCL blends does not significantly change until 30 wt.% of PCL is added to PLA, a composition that shows a value almost double to that of neat PLA.…”
Section: Reference Noncompatibilized Pla/pcl Blends: Influence Of Pcl...mentioning
confidence: 79%
“…In noncompatibilized PLA/PCL blends, it is observed that the modulus decreases linearly as the amount of PCL increases (Figure 1a), which is typical for PLA/PCL systems. [12,18,20,37] Similarly, the yield strength also decreases with increasing the PCL content, showing a negative deviation from the additive law for mixtures.…”
Section: Reference Noncompatibilized Pla/pcl Blends: Influence Of Pcl...mentioning
confidence: 95%
See 1 more Smart Citation
“…1,2 Poly(butylene succinate) (PBS) is a biodegradable aliphatic polyester material with high processability, excellent thermal stability, and close to general plastics in mechanical properties. 1,2 Poly(butylene succinate) (PBS) is a biodegradable aliphatic polyester material with high processability, excellent thermal stability, and close to general plastics in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, environmental-friendly materials based on renewable resources, in particular biodegradable polymers, have been a particular focus of research among the environment sustainability. 1,2 Poly(butylene succinate) (PBS) is a biodegradable aliphatic polyester material with high processability, excellent thermal stability, and close to general plastics in mechanical properties. [3][4][5] Therefore, PBS is a type of ideal plastic matrix for the preparation of biodegradable composites.…”
Section: Introductionmentioning
confidence: 99%